The Role of Podocyte Cells in Diabetic Nephropathy: A Narrative Literature Review - Fauzan Azhari; Novadian; Ian Effendi; Zulkhair Ali; Suprapti; Ratna Maila Dewi Anggraini; Yulianto Kusnadi; Alwi Shahab (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
The main cells affected in diabetic nephropathy are podocytes and proximal tubular cells. One of the main functional proteins in the podocyte slit diaphragm is podocin which podocytes need to express together with several specific proteins in the correct way for their differentiation, as well as to maintain their complex anatomy. Podocytes are highly specialized epithelial cells. They line the urinary surface of the glomerular capillary bundles. Podocytes are part of the filtration barrier along with capillary endothelial cells and GBM. Podocytes ensure selective permeability of the glomerular capillary walls. Podocin is a membrane protein with a molecular weight of 42kD which is located in the foot processes, and also forms part of the SD with the nephrin protein. Urinary podocin levels more specifically indicate ongoing glomerular damage because they were significantly increased in the normoalbuminuria group compared with the control group.